Ultrasound Tomography: Preliminary Result (Jurnal Teknologi (Sciences & Engineering), 2012)
This paper presents the initial result of an investigation into the application of ultrasonic sensors for a tomographic imaging system. Transmitters and receivers are mounted permanently on the inner part of the vertical flow pipe. To overcome the problems of objects blocking each other, four pairs of sensors are used, mounted around the area of interest, and views from different angles are obtained. The results obtained show that the system is capable of detecting particle flow. Key words: Ultrasound tomography